Rebooting the Guidelines for the Education of Library Technicians - Erickson, Norene; Shamchuk, Lisa (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2023)
The Canadian Federation of Library Association’s (CFLA-FCAB) Guidelines for the Education of Library Technicians were last updated in 2011 and in need of a reboot. These guidelines have helped to establish a national standard for the education of library technicians in Canada and provided a framework for the development of skills, knowledge, and abilities of library technicians to provide job-ready, and highly skilled graduates. As much has changed in the library and information landscape in recent years, we instigated a substantial update to the Guidelines in 2021. The update was completed and approved by the CFLA-FCAB in July 2022 and is a guide for library educators, library administrators, supervisors, and practitioners. This paper details the research process undertaken to update the Guidelines that reflect the core competencies of library technicians in Canada.